2022
DOI: 10.1262/jrd.2022-058
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of pig spermatozoa using carboxylated poly-L-lysine as cryoprotectant

Abstract: In this study, we cryopreserved pig spermatozoa using carboxylated poly-L-lysine (CPLL) as the cryoprotectant to determine its efficacy. Pig spermatozoa were placed in a freezing extender containing 3% (v/v) glycerol and different CPLL concentrations. The motility indices of the spermatozoa cryopreserved with 0.25% (v/v) CPLL at 6 (59.3), 9 (53.7), and 12 (26.2) h after thawing were significantly higher (P < 0.01 or P < 0.05) than those of the spermatozoa cryopreserved without CPLL (53.7, 40.1, and 17.5 at 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The addition of DMGA-PLL to the freezing extender may have increased the chance that ovulated oocytes would encounter fertile spermatozoa because the treatment improved the motility of spermatozoa at 12 h after thawing. Our previous study investigating the ability of spermatozoa cryopreserved with glycerol and CPLL to produce offspring after AI showed that the mean number of total piglets was significantly lower than that produced by sows inseminated with spermatozoa stored at 17 C. In addition, the mean number of live piglets tended to be lower (Jin et al, 2022). In contrast, in this study, there were no significant differences in the mean numbers of total and live piglets between spermatozoa cryopreserved with glycerol and DMGA-PLL and those stored For AI-based pig production on commercial farms, it is crucial to obtain as many live piglets as possible from inseminated sows.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The addition of DMGA-PLL to the freezing extender may have increased the chance that ovulated oocytes would encounter fertile spermatozoa because the treatment improved the motility of spermatozoa at 12 h after thawing. Our previous study investigating the ability of spermatozoa cryopreserved with glycerol and CPLL to produce offspring after AI showed that the mean number of total piglets was significantly lower than that produced by sows inseminated with spermatozoa stored at 17 C. In addition, the mean number of live piglets tended to be lower (Jin et al, 2022). In contrast, in this study, there were no significant differences in the mean numbers of total and live piglets between spermatozoa cryopreserved with glycerol and DMGA-PLL and those stored For AI-based pig production on commercial farms, it is crucial to obtain as many live piglets as possible from inseminated sows.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous study investigating the ability of spermatozoa cryopreserved with glycerol and CPLL to produce offspring after AI showed that the mean number of total piglets was significantly lower than that produced by sows inseminated with spermatozoa stored at 17°C. In addition, the mean number of live piglets tended to be lower (Jin et al, 2022). In contrast, in this study, there were no significant differences in the mean numbers of total and live piglets between spermatozoa cryopreserved with glycerol and DMGA‐PLL and those stored at 17°C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations